Preparation method of BVO / CoPc + BN composite photo-anode and application of BVO / CoPc + BN composite photo-anode in photoelectrochemical decomposition of water
By loading boron nitride and cobalt phthalocyanine composite materials on the bismuth vanadate photoanode to form a BVO/CoPc+BN composite photoanode, the problem of limited performance of bismuth vanadate in photoelectrochemical decomposition of water is solved, and efficient photocurrent density and water oxidation activity are achieved.
Patent Information
- Application Number
- CN202411913443.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In practical applications, bismuth vanadate has problems such as poor conductivity, severe charge recombination, and slow surface dynamics, which limits its photoelectrochemical decomposition of water.
BVO/CoPc+BN composite photoanode was prepared, and the composite material was formed by mixing boron nitride (BN) and cobalt phthalocyanine (CoPc) and loading it onto bismuth vanadate (BVO) to form a composite material, promoting the separation of photogenerated carriers and water oxidation activity.
Under 1.23V vs RHE conditions, the BVO/CoPc+BN composite photoanode exhibits excellent photocurrent density, which is much higher than the water oxidation photocurrent density of BVO alone, and has the potential to be applied to photoelectric and water oxidation reactions.
Smart Images

Figure CN119736667A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photoanodes, and in particular to a method for preparing a BVO / CoPc+BN composite photoanode and application thereof in photoelectrochemical water decomposition. Background Art
[0002] In practical applications, bismuth vanadate (BVO) has poor conductivity, severe charge recombination, and slow surface dynamics, so its PEC performance is still limited. Therefore, in the construction of bismuth vanadate-based composite photoanodes, the multi-layered and multi-component assembly method has been discussed by most researchers. In most cases, in the multi-component bismuth vanadate-based composite photoanodes, one component assists in improving the transfer of photogenerated carriers, while the remaining components act as OECs to enhance the water oxidation activity of BVO. This shows that in order to assist BVO in completing an efficient oxygen evolution reaction, the synergistic effect between multiple components is crucial.
[0003] In this research context, we consider selecting a layered material that can promote the separation of photogenerated carriers and a layered material with efficient water oxidation activity, and assembling them into a thinner layered composite material. In addition, the layered composite material needs to be controlled to a thinner thickness to ensure that each layered material can still fully play its role without increasing the hole transmission distance, and achieve the superposition effect of multiple effects. Subsequently, it is loaded onto BVO through appropriate modification methods, and the formed BVO-based composite photoanode is theoretically expected to assist BVO in achieving efficient oxygen evolution reaction.
[0004] Among various two-dimensional nanomaterials, boron nitride (BN) nanosheets, which are called "white graphene" due to their similarity to graphene, are honeycomb structures composed of covalently bonded boron and nitrogen atoms. It has excellent properties, including extremely high oxidation resistance and good chemical inertness, high thermal conductivity, high melting point and high specific surface area, especially under relatively harsh conditions, it can avoid sintering of supported catalysts on hot spots, so it is expected to become a carrier material for catalysts. In addition to the inherent properties of BN, BN with rich pores and large specific surface area has shown some innovative applications in hydrogen storage and water purification. Based on this, it is believed that BN can be used as a hole transport layer to achieve the effect of inhibiting the recombination of photogenerated electron-hole pairs.
[0005] As a versatile class of organic functional dyes, metal phthalocyanines (MPcs) have great potential for use as electrocatalysts due to their interesting and tunable optical and electronic properties. When these transition metal complexes are modified on the surface of semiconductors, their molecular orbitals will overlap with the electronic energy bands of the semiconductor, which will reduce the energy barrier of the OER reaction and improve the PEC performance. In addition, these molecular / semiconductor hybrid photoanodes can be manufactured and controlled using a much simpler preparation process. On the other hand, phthalocyanine is a planar macrocyclic structure with a large conjugated electron system, which can easily coordinate with transition metal cations to form stable metal complexes due to the presence of four central nitrogen atoms. Therefore, cobalt phthalocyanine (CoPc) has great potential as OECs in theory. Summary of the invention
[0006] The present invention prepares a BN+CoPc composite material, which is then loaded onto BVO to form a BVO / BN+CoPc composite photoanode. Under a potential of 1.23 V vs RHE, the BVO / CoPc+BN composite photoanode exhibits an excellent photocurrent density of 5.04 mA cm -2 A series of characterizations and tests have proven that the BN+CoPc composite material can not only promote the separation of photogenerated carriers, but also achieve a water oxidation photocurrent density much higher than that of BVO alone during 3h of electrolysis. This confirms its potential for use in the use of light and electricity for hydrogen and oxygen evolution reactions in real situations.
[0007] The technical solution of the present invention is as follows: a BVO / CoPc+BN composite photoanode, the preparation method of which comprises the following steps:
[0008] 1) Preparation of CoPc+BN composite material: boron nitride BN and cobalt phthalocyanine CoPc were mixed, acetonitrile was added, ultrasonication was performed, stirring was performed, centrifugation was performed, the supernatant was discarded, the product obtained by centrifugation was placed in a crucible, calcined, and ground to obtain the CoPc+BN composite material;
[0009] 2) Preparation of BVO / CoPc+BN composite photoanode: N,N-dimethylformamide was added to the CoPc+BN composite material, and deionized water was added. The ultrasonic treatment was continued until no precipitate was produced. The mixed solution was poured into a hydrothermal reactor, and BVO was added to carry out a hydrothermal reaction. After the reaction was completed, the solution was washed and dried to obtain a BVO / CoPc+BN composite photoanode.
[0010] In the above-mentioned BVO / CoPc+BN composite photoanode, in step 1), the mass ratio of boron nitride BN to cobalt phthalocyanine CoPc is 4:1 to 8:1.
[0011] In the above-mentioned BVO / CoPc+BN composite photoanode, in step 1), the mass ratio of boron nitride BN to cobalt phthalocyanine CoPc is 6:1.
[0012] In the above-mentioned BVO / CoPc+BN composite photoanode, in step 1), the calcination is carried out by heating the temperature to 300°C at a heating rate of 5°C / min and calcining at 300°C for 2h.
[0013] In the above-mentioned BVO / CoPc+BN composite photoanode, in step 2), the hydrothermal reaction is carried out at 80° C. overnight.
[0014] The above-mentioned BVO / CoPc+BN composite photoanode is applied in electrochemical water decomposition.
[0015] For the above application, the method is as follows: at 0.6 V vs RHE, 100 mW cm -2 The simulated sunlight device is used as a light source to carry out a photoelectric water oxidation reaction, the BVO / CoPc+BN described in claim 1 is used as a working electrode, a platinum wire is used as a counter electrode, and Ag / AgCl is used as a reference electrode to carry out photoelectric water splitting to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the SEM image of CoPc+BN.
[0017] Figure 2 (a) is the SEM image of BVO, and (b) is the SEM image of BVO / CoPc+BN.
[0018] Figure 3 XPS of (a) Bi 4f, (b) V 2p and (c) O 1s of BVO and BVO / CoPc+BN.
[0019] Figure 4 XRD patterns of BVO and BVO / CoPc+BN.
[0020] Figure 5 (a) is the XRD pattern of the CoPc+BN composite material in Example 1 and the uncalcined CoPc+BN material in Comparative Example 1; (b) is the XRD pattern of BN, CoPc and a series of CoPc+BN materials prepared at different feed ratios.
[0021] Figure 6 (a) and (b) LSV plots of different BVO-based composite photoanodes.
[0022] Figure 7(a) ABPE diagram, (b) charge transfer efficiency diagram, and (c) EIS spectrum of four photoanodes: BVO, BVO / BN, BVO / CoPc, and BVO / CoPc+BN.
[0023] Figure 8 IT diagrams of BVO and BVO / CoPc+BN. DETAILED DESCRIPTION
[0024] The present invention adopts the experimental steps of ultrasonic stripping followed by high-temperature sintering to combine boron nitride with cobalt phthalocyanine organic matter to form a thin layer composite material, namely CoPc+BN. The thickness stripping of the layered two-dimensional material is achieved by ultrasonic means. The introduction of boron nitride ensures the stability of cobalt phthalocyanine during the sintering process and promotes the crystal structure integrity of the generated CoPc+BN composite material. Subsequently, the composite material loaded with CoPc+BN is coated on the BVO photoanode to form a BVO / CoPc+BN composite photoanode.
[0025] Example 1 Preparation of BVO / CoPc+BN Photoanode
[0026] 1. Preparation of CoPc+BN composites
[0027] First, add the BN and CoPc mixture into a beaker in a ratio of m(BN):m(CoPc)=4:1, 6:1, and 8:1, then pour 60mL of acetonitrile solvent into the beaker and ultrasonicate for 3h. Then add a rotor to the beaker and stir overnight. Centrifuge at 8000rpm for five minutes, separate the mixture and solvent with a centrifuge, and pour off the supernatant. Put the product obtained by centrifugation into a crucible, heat it to 300℃ in a muffle furnace at a heating rate of 5℃ / min, and calcine it at 300℃ for 2h. Finally, grind the product obtained after calcination to obtain a CoPc+BN composite material.
[0028] 2. Preparation of BVO / CoPc+BN Photoanode
[0029] Weigh 0.03g of CoPc+BN composite material into a beaker, then pour 5mL of N,N-dimethylformamide solvent into the beaker and ultrasonicate for 1h. Pour 15mL of deionized water into the solution and continue ultrasonicating for 1h until there is no precipitate at the bottom. Pour the mixed solution into a hydrothermal reactor, then put BVO into the hydrothermal reactor and react overnight at 80°C. After the reaction is completed, take out BVO, rinse it repeatedly with deionized water, and then blow dry it with N2 to obtain a BVO / CoPc+BN photoanode.
[0030] Comparative Example 1 CoPc+BN uncalcined material
[0031] First, add the BN and CoPc mixture into a beaker at a ratio of m(BN):m(CoPc)=6:1, then pour 60mL of acetonitrile solvent into the beaker and ultrasonicate for 3h. Then add a rotor to the beaker and stir overnight. Centrifuge at 8000rpm for five minutes, separate the mixture and solvent with a centrifuge, and pour off the supernatant. Put the product obtained by centrifugation into a 60℃ oven, and finally grind the product obtained after drying to obtain an uncalcined CoPc+BN composite material.
[0032] Comparative Example 2 Preparation of BVO / CoPc Photoanode
[0033] Weigh 0.03g of CoPc composite material into a beaker, then pour 5mL of N,N-dimethylformamide solvent into the beaker and ultrasonicate for 1h. Pour 15mL of deionized water into the solution and continue ultrasonicating for 1h to obtain a uniform dispersion. Pour the mixed solution into a hydrothermal reactor, then put BVO into the hydrothermal reactor and react overnight at 80°C. After the reaction is completed, take out BVO, rinse it repeatedly with deionized water, and then blow dry it with N2 to obtain a BVO / CoPc photoanode.
[0034] Comparative Example 3 Preparation of BVO / BN Photoanode
[0035] Weigh 0.03g of hexagonal boron nitride into a beaker, then pour 5mL of N,N-dimethylformamide solvent into the beaker and ultrasonicate for 1h. Pour 15mL of deionized water into the solution and continue ultrasonicating for 1h to obtain a uniform dispersion. Pour the mixed solution into a hydrothermal reactor, then put BVO into the hydrothermal reactor and react overnight at 80°C. After the reaction is completed, take out BVO, rinse it repeatedly with deionized water, and then blow dry it with N2 to obtain a BVO / BN photoanode.
[0036] Example 2 Characterization of BVO / CoPc+BN Photoanode
[0037] 1. Material Characterization
[0038] By observation Figure 1 Scanning electron microscope (SEM) images of the CoPc+BN composite material show that the material exhibits an irregular morphology. This morphological feature may be due to the different degrees of fragmentation of the material during the ultrasonic process, but this process also provides more active sites for the oxygen evolution reaction. When further observing the microscopic morphology of the BVO / CoPc+BN composite material ( Figure 2 ), and found that the hydrothermal method of loading CoPc+BN onto BVO did not affect the porous morphology of BVO, while keeping the CoPc+BN at a relatively thin thickness. This loading method provides a shorter transmission path for hole transport, effectively promoting the oxygen evolution reaction.
[0039] To determine the chemical state of the samples, X-ray photoelectron spectroscopy (XPS) was performed on the BVO and BVO / CoPc+BN photoanodes. Figure 3 It can be seen that when CoPc+BN is loaded onto BVO, the Bi 4f, V 2p and O1s peaks all shift to a certain extent, indicating that CoPc+BN interacts with BVO, resulting in changes on the BVO surface.
[0040] In addition, by comparing the X-ray diffraction (XRD) patterns of BVO and BVO / CoPc+BN ( Figure 4 ) found that they have the same diffraction peaks, indicating that the loading of CoPc+BN does not affect the monoclinic crystal structure of BVO. No peaks representing the characteristics of BN or CoPc were observed in the XRD pattern of BVO / CoPc+BN, further illustrating the thin nature of the CoPc+BN catalytic layer.
[0041] In order to further explore the changes in the crystal structure of CoPc+BN after calcination or without calcination, the materials were fed according to the mass ratio of m(BN):m(CoPc)=6:1, and were processed in two parts during the synthesis process. One part was not calcined at high temperature, only centrifuged and dried at room temperature, and the other part was calcined. Subsequently, the two parts of the material were ground to the same degree. By comparing the XRD spectra before and after calcination, such as Figure 5 As shown in (a), it was found that the crystallinity of the CoPc+BN composite material calcined at 300°C was significantly better than that of the uncalcined material, indicating that the CoPc+BN formed by calcination has a more uniform lattice structure and provides a more uniform catalytic environment.
[0042] In addition, a series of powder composite catalysts CoPc+BN were obtained under the same preparation conditions by feeding materials according to different mass ratios (m(BN):m(CoPc)=4:1, 6:1, 8:1). Figure 5 The XRD spectrum in (b) shows that the crystallinity of the composite material is the highest when the mass ratio is m(BN):m(CoPc)=6:1. Therefore, it is theoretically speculated that the composite material is more effective in photoelectrochemical water splitting.
[0043] Example 3 Photoelectrochemical water splitting performance test
[0044] At 0.6 V vs RHE, 100 mW cm -2The simulated sunlight device was used as the light source to carry out the photoelectric water oxidation reaction, with the composite photoanode prepared in Example 1 as the working electrode, the platinum wire as the counter electrode, and the Ag / AgCl as the reference electrode. After half an hour of electrolysis, 100 microliters of gas was extracted with a gas injection needle and injected into the gas chromatograph. Waiting for the analysis results. It was found that the accumulated hydrogen production was 25.6 μmol within half an hour.
[0045] To verify the above theory, separate BN and CoPc as well as different CoPc+BN materials were loaded onto bismuth vanadate to form different BVO-based composite photoanodes, and linear sweep voltammetric cycling tests were performed under AM1.5G illumination. Figure 6 The linear sweep voltammetry (LSV) curve in (a) found that loading BN or CoPc on BVO alone cannot effectively assist BVO in achieving efficient water oxidation reaction, but when BN and CoPc are combined and then loaded on bismuth vanadate, the oxygen evolution reaction effect is significantly increased. This result further verifies the excellence of multi-components in photoelectric water splitting applications. According to previous inferences, when the initial feed m(BN):m(CoPc)=6:1, the BVO / CoPc+BN composite material loaded on BVO to form a composite photoanode should exhibit the best water oxidation activity. Figure 6 The test results in (b) confirm the above inferences and further demonstrate the superiority of the structural uniformity of the CoPc+BN composite material for the multi-component synergistic assistance of BVO for oxygen evolution reaction.
[0046] According to formula (1), the applied bias light-to-electricity conversion efficiency (ABPE) curves of different bismuth vanadate-based composite photoanodes were plotted. Figure 7 (a) clearly shows the electrochemical performance of each sample. After analyzing the data, it can be seen that BVO reaches a maximum ABPE value of 0.34% at 0.88V vs RHE. In contrast, BVO / BN presents a maximum ABPE value of 0.63% at 0.83V vs RHE, while BVO / CoPc achieves a maximum ABPE value of 1.41% at 0.72V vs RHE. Remarkably, the maximum ABPE value of BVO / CoPc+BN far exceeds that of previous samples, reaching an ABPE value of 1.83% at only 0.67V vs RHE. This discovery reveals the advantage of multi-component oxygen co-catalysts, which is the ability to achieve higher solar energy conversion efficiency at lower bias voltages.
[0047]
[0048] In order to explore the effect of multiple components on the charge transfer efficiency of bismuth vanadate, 0.2M sodium sulfite was added to the electrolyte to ensure that the photogenerated holes reacted with Na2SO3 as much as possible in the LSV test, thereby obtaining the J(Na2SO3) value. According to the derived formula (2), the charge transfer efficiency curve was plotted. Figure 7 It is clearly seen in (b) that in the range of 0.4 V to 1.23 V vs RHE, the charge transfer efficiency of the composite photoanode formed by loading BN or CoPc onto BVO alone is significantly lower than that of the multi-component composite photoanode formed by CoPc+BN and BVO (η trans =76%, 1.23 V vs RHE). This result shows the importance of multi-component composite materials in improving the charge transfer efficiency.
[0049]
[0050] The excellent performance of the multi-component composite photoanode BVO / CoPc+BN in promoting charge transfer was further demonstrated by conducting impedance spectroscopy (EIS) tests. Figure 7 (c) shows that the order of the diameter of the impedance semicircle is: BVO>BVO / BN>BVO / CoPc>BVO / CoPc+BN. A smaller impedance semicircle radius means a faster charge transfer rate at the material interface, thereby improving the charge transfer efficiency. Therefore, it can be concluded that both CoPc and BN can promote the improvement of the charge transfer rate, and when they are combined together, they can better accelerate the charge transfer at the material interface. This result once again verifies the superiority of multi-component materials in promoting charge transfer.
[0051] According to the previous analysis, BVO achieved the maximum ABPE value at 0.88V vs RHE, while BVO / CoPc+BN showed the highest external bias photoelectric conversion efficiency at 0.67V vs RHE. Therefore, BVO was electrolyzed at 0.8V vs RHE and BVO / CoPc+BN was electrolyzed at 0.6V vs RHE for 3 hours. The chronoamperometric (it) curves were as follows: Figure 8 As shown in the figure, it can be seen that after being modified by CoPc+BN, BVO can maintain a water oxidation performance far higher than that of BVO for a long period of time. This confirms its potential for application in photoelectric water oxidation.
[0052] Through the above experimental observations and analysis, it can be concluded that the loading of CoPc+BN composite material has a significant promoting effect on the water oxidation activity of bismuth vanadate (BVO) photoanode. Through scanning electron microscopy observation, it was found that the CoPc+BN composite material showed an irregular morphology, but its loading on BVO did not affect the porous morphology of BVO, and it could provide a shorter transmission path, effectively promoting the oxygen evolution reaction. X-ray diffraction patterns showed that the loading of CoPc+BN did not affect the monoclinic crystal structure of BVO, and the CoPc+BN formed by calcination had a more uniform lattice structure, providing a more uniform catalytic environment. In addition, the highest crystallinity of the composite material under different mass ratios was m(BN):m(CoPc)=6:1, which was consistent with theoretical speculation that the composite material had a better effect in photoelectrochemical water splitting. LSV test results showed that the BVO / CoPc+BN composite material exhibited the best water oxidation activity, further verifying the superiority of the uniformity of the structure of the CoPc+BN composite material for the multi-component synergistic assistance of BVO for oxygen evolution reaction. Subsequent electrochemical performance tests further confirmed the superior performance of BVO / CoPc+BN in promoting charge transfer.
[0053] In summary, CoPc+BN composite materials as auxiliary catalysts can effectively improve the water oxidation activity and electrolytic stability of bismuth vanadate-based composite photoanodes, providing new research ideas and methods for practical applications in the fields of solar energy conversion and water splitting. However, further optimization is still needed in the synthesis and preparation of the composite material to improve its performance in practical applications and make greater contributions to the development of sustainable energy.
Claims
1. A BVO / CoPc+BN composite photoanode, characterized in that: The preparation method comprises the following steps: 1) Preparation of CoPc+BN composite material: boron nitride BN and cobalt phthalocyanine CoPc were mixed, acetonitrile was added, ultrasonication was performed, stirring was performed, centrifugation was performed, the supernatant was discarded, the product obtained by centrifugation was placed in a crucible, calcined, and ground to obtain the CoPc+BN composite material; 2) Preparation of BVO / CoPc+BN composite photoanode: N,N-dimethylformamide was added to the CoPc+BN composite material, and deionized water was added. The ultrasonic treatment was continued until no precipitate was produced. The mixed solution was poured into a hydrothermal reactor, and BVO was added to carry out a hydrothermal reaction. After the reaction was completed, the solution was washed and dried to obtain a BVO / CoPc+BN composite photoanode.
2. A BVO / CoPc+BN composite photoanode according to claim 1, characterized in that: In step 1), the mass ratio of boron nitride BN to cobalt phthalocyanine CoPc is 4:1 to 8:
1.
3. A BVO / CoPc+BN composite photoanode according to claim 2, characterized in that: In step 1), the mass ratio of boron nitride BN to cobalt phthalocyanine CoPc is 6:
1.
4. The BVO / CoPc+BN composite photoanode according to claim 1, characterized in that: In step 1), the calcination is carried out by heating the temperature to 300° C. at a heating rate of 5° C. / min and calcining at 300° C. for 2 h.
5. The BVO / CoPc+BN composite photoanode according to claim 1, characterized in that: In step 2), the hydrothermal reaction is carried out at 80° C. overnight.
6. Application of the BVO / CoPc+BN composite photoanode described in claim 1 in electrochemical water decomposition.
7. The use according to claim 6, characterized in that: The method is as follows: at 0.6 V vs RHE, 100 mW cm -2 The simulated sunlight device is used as a light source to carry out a photoelectric water oxidation reaction, the BVO / CoPc+BN described in claim 1 is used as a working electrode, a platinum wire is used as a counter electrode, and Ag / AgCl is used as a reference electrode to carry out photoelectric water splitting to produce hydrogen.
Citation Information
Patent Citations
Preparation method of BiVO4 / CoF2 photo-anode
CN114196986A
Preparation method and application of BiVO4 / Co (OH) F / FeOOH composite photo-anode
CN116121803A
Phthalocyanine-based ternary composite photoelectric catalyst as well as preparation method and application thereof
CN116970986A
Core-shell structure bismuth vanadate and cobalt phthalocyanine composite photoelectrode and preparation method and application thereof
CN117127212A
Organic-inorganic composite catalyst photo-anode and preparation method and application thereof
CN117966209A
Cited By
Perfluoromanganese phthalocyanine composite bismuth vanadate photoelectrode, preparation method thereof and application of photoelectrode in synthesis of formamide from biomass through photoelectrocatalysis
CN120272956A